Non-linear shallow water models for coastal run-up simulations - Macías-Sánchez, Jorge; González-Vida, José Manuel; Castro-Díaz, Manuel Jesús (European Geosciences Union, 2013)
Shallow water models are frequently used to simulate ocean or coastal circulation or tsunami wave propagation. But these models are seldom used to explicitely reproduce for example tsunami wave run-up into coast. In this work we porpose an implementation of dry/wet areas for shallow water models that allow to reproduce coastal inundation and water retrainment once the impact wave passes over. The run-up model has been tested for simple test cases and geometries as in complex, real cases, as the Lituya Bay 1958 megatsunami.
Keywords: Maremotos - Métodos de simulación; Circulación oceánica - Métodos de simulación; Numerical Simulation; run-up simulations; Monai Valley; shallow water models